Kualitas Hidup Lansia Di Panti Jompo Rumah Bahagia Bintan - Dea Sadariah; Yurni Jusiani; Suryaningsih . (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2026)
The aging process, characterized by a decline in physical, psychological, and social abilities, makes the elderly a vulnerable group to various life problems. This study examines the quality of life of the elderly at the Rumah Bahagia Bintan Nursing Home based on physical, psychological, social, and environmental aspects. This study aims to analyze the quality of health and life of the elderly at the Rumah Bahagia Bintan Nursing Home through physical, psychological, social, and environmental aspects using the WHOQOL-BREF instrument to provide an in-depth overview of the quality of life of the elderly. This research method is descriptive qualitative, to collect data, observation, in-depth interviews, and documentation are used. Research information comes from the elderly who live in the nursing home and the nursing home manager. This study was conducted at the Rumah Bahagia Bintan Nursing Home in Bintan Regency, Riau Islands Province, from July to August 2025. The study results indicate that the quality of life of the elderly at the Rumah Bahagia Bintan Nursing Home is in the moderate to good category. Physical aspects indicate a decline in body function due to the aging process, but are supported by adequate health services and the fulfillment of basic needs. Psychological, social, and environmental aspects indicate a relatively stable condition with social support, interaction between residents, and a safe and comfortable home environment. The role of the Nursing Home is very important in supporting the well-being of the elderly, although improvements in services, particularly in psychological support and family involvement, still need to be optimized.